Associations of myeloperoxidase, interleukin-17A and heparin-binding EGF-like growth factor levels with in-stent restenosis after percutaneous coronary intervention: a single-centre case–control study in China. Issue 11 (6th November 2020) - Jiang, Hua; Zhang, Hongmei; Yang, Ying; Yang, Xuezhou
Abstract : Objectives: To investigate the changes in serum myeloperoxidase (MPO), interleukin (IL)-17A and heparin-binding EGF-like growth factor (HB-EGF) levels before and after percutaneous coronary intervention (PCI), and to evaluate the associations of MPO, IL-17A and HB-EGF levels with the 1-year restenosis rate. Design: Case–control study. Settings: Xiangyang Central Hospital between January 2012 and December 2017. Participants: Patients with coronary heart disease who underwent PCI. Interventions: Not applicable. Primary and secondary outcome measures: Not applicable. Results: Finally, 407 and 132 patients were included in the control and in-stent restenosis (ISR) groups, respectively. The general clinical characteristics of the patients were not significantly different between the two groups. The MPO, IL-17A and HB-EGF levels were not significantly different between the two groups at baseline but significantly increased after PCI. The ISR group showed higher levels of MPO, IL-17A and HB-EGF compared with the control group at all postoperative time points. Multivariable analysis showed that MPO, IL-17A and HB-EGF were associated with increased ISR [MPO (OR=1.003; 95% CI: 1.001 to 1.005; p=0.002), IL-17A (OR=1.015; 95% CI: 1.009 to 1.020; p<0.0001) and HB-EGF (OR=2.256; 95% CI: 1.103 to 4.009; p=0.002)]. All three factors had sensitivity and specificity ≥68% for ISR. Conclusions: HB-EGF could be used for the detection of ISR after PCI and could be of use for the prediction of ISR, but the value of MPO and IL-17A might be more limited. This will have to be validated in future studies.